PENGARUH KEPERCAYAAN, PELAYANAN, DAN PRODUK TERHADAP MINAT MENJADI ANGGOTA KSPPS BINA SYARIAH UMMAH DUKUN GRESIK - Suwaldiyana , Suwaldiyana (IQTISODINA, 2022)
This research was conducted to analyze the effect of trust, service, and products on interest in becoming a member of KSPPS Bina Syariah Ummah Dukun Gresik. The data used in this study are members of the KSPPS Bina Syariah Ummah Branch of the Shaman in 2020-2021. This type of research is quantitative research and the analytical technique used in this study is multiple linear regression with the help of the SPSS 25.0 for windows program. The results of this study indicate that partially the variables of Trust, Service, and Products have a significant effect on the interest variable to become a member of KSPPS Bina Syariah Ummah Dukun Gresik. whereas, Simultaneously the variables of Trust, Service and Products also have a significant effect on Interest in becoming a member of KSPPS Bina Syariah Ummah Dukun Gresik. Based on the results of the research above, the researcher recommends being able to increase socialization more about KSPPS Bina Syariah Ummah Dukun Gresik to the community, especially among small traders, in public places. So that they know very well about KSPPS Bina Syariah Ummah Dukun Gresk and its products.